Wnt antagonist, secreted frizzled-related protein 4 (sFRP4), increases chemotherapeutic response of glioma stem-like cells - Warrier, S.; Balu, S.; Kumar, Alan Prem; Michael, M.; Dharmarajan, Arunasalam (Cognizant Communication Corporation, 2014)
Malignant gliomas have a highly tumorigenic subpopulation, termed cancer stem cells (CSCs), that drives tumor formation and proliferation. CSCs possess inherent resistance mechanisms against radiation- and chemotherapy- induced cancer cell death, enabling them to survive and initiate tumor recurrence. We examined the effect of secreted frizzled-related protein 4 (sFRP4), a Wnt signaling antagonist, in chemosensitizing the glioma cell line U138MG and glioma stem cells (GSCs) enriched from U138MG to chemotherapeutics. We found that sFRP4 alone and in combination with either doxorubicin or cisplatin induced apoptosis. Proliferation decreased substantially in GSC-enriched population as measured by MTT and BrdU assays. JC-1 and caspase- 3 assays demonstrated that cell death was through the apoptotic pathway. sFRP4 treatment also decreased neurosphere formation and induced neuronal differentiation. Inhibition by sFRP4 was abolished by Wnt3a, indicating that sFRP4 acts through the frizzled receptor. Further indication that sFRP4 acts through the Wnt b-catenin pathway was provided by decrease in the b-catenin protein and decrease in the b-catenin-stimulatedgene cyclin D1 upon sFRP4 induction. By real-time PCR, an increase in apoptotic markers Bax and p21, a decrease in pro-proliferative marker CycD1, and a decrease in the GSC marker CD133 were observed. These observations indicate that sFRP4 is able to sensitize glioma cells and stem cells to chemotherapeutics. We thus identified for the first time that sFRP4 could help to destroy cancer stem cells of glioma cell line, which would lead to effective treatment regimen to combat brain tumors.